Network Planning to Organic Growth: Understanding Settlement Dynamics in Frankfurt and Surabaya (Architecture Image Studies, 2025)
This study examines the differences in settlement dynamics between Frankfurt (Germany), which developed using a planned grid pattern, and Surabaya (Indonesia), which grew organically. The research focuses on the historical, policy, and socio-cultural factors that shaped these two settlement patterns, as well as their socioeconomic impacts on residents' quality of life. Using a mixed-methods approach, the study combines spatial analysis, policy document review, and field data collection to understand the contrast between a designed grid system and an adaptive, organic growth model. Findings demonstrate that Frankfurt’s grid layout is designed for spatial efficiency and accessibility, while Surabaya’s organic shape is better suited to respond to human pressures and infrastructure constraints. Some of the impacts identified are: unequal provision of basic services and limited mobility in Surabaya; problems in integrating planning policy. The study offers policy recommendations for inclusive and sustainable settlement development, while also strengthening cross-continental collaboration in urban studies.In the context of urbanization and urban development, Frankfurt in Germany and Surabaya in Indonesia represent two interesting case studies of settlement dynamics and urban growth. Both cities demonstrate different yet relevant approaches to addressing the challenges of modernization, population density, and key infrastructure needs, including housing, transportation, and other public facilities.